Civil wars in South Asia : state, sovereignty, development - Sundar, Aparna; Sundar, Nandini (New Delhi : SAGE, 2016)
This volume demonstrates the importance of South Asia as a region to deepening the study of civil wars and armed conflicts and, simultaneously, illustrates how civil wars open up questions of sovereignty, citizenship and state contours. By engaging these broader theoretical debates, in a field largely dominated by security studies and comparative politics, it contributes to the study of civil wars, political sociology, anthropology and political theory.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 25, 2016).
Keywords: Social conflict -- South Asia; Conflict management -- South Asia; Civil War -- South Asia; South Asia -- Politics and government -- 20th century; South Asia -- Politics and government -- 21st century